Transitions in Vocational Education - Seifried, Jürgen [Herausgeber]; Wuttke, Eveline [Herausgeber] (Barbara Budrich, 2013)
"This volume focuses on the different passages and transitions in Vocational Education and professional work life. Exploring the personal experiences of coping with the transition from school to vocational education, vocational education to work, and - finally - within work life, the book takes account of the rapidly changing conditions under which these processes take place." The contributions in this book span the range from highly regulated and corporative structured vocational educational systems (eg. Germany, Switzerland) to largely deregulated systems (Uk, Australia). Despite these differences, young people experience a similar level of difficulty entering the workforce, training programmes or higher education programmes. (Verlag, BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; I 2.2 Europa; Berufseinmündung; Erste Schwelle; Zweite Schwelle; Berufliche Integration; Berufsausbildung; Übergangssystem; Hochschulbildung; Beschäftigungsfähigkeit; Berufsbildungssystem; Bundesrepublik Deutschland; Schweiz; Niederlande; Österreich; Italien; Spanien; Portugal; Großbritannien; Australien